Delivery system and performance level of grade 8 learners in technology and livelihood education: basis for a proposed intervention plan - Erandio, Racquel F. (2020)
This study aims to assess the delivery system of Technology and Livelihood Education program, its efficiency and relative problems being encountered by the implementers. The data proposed intervention plan. The intervention plan will be made to ensure that the needs of the program for efficient implementation will be achieved.
Thesis (MA in Education major in Administration and Supervision)--Eulogio "Amang" Rodriguez Institute of Science and Technology, Manila, 2020
Keywords: Educational technology; TLE -- Study and teaching